2020
DOI: 10.1055/a-1143-8521
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of the Potential Effects of Nigella sativa on Rheumatoid Arthritis

Abstract: Considering the different untoward effects of the drugs prescribed for the treatment of rheumatoid arthritis (RA), there has been an increasing interest in adjuvant therapies devoid of such unfavorable reactions. Although the beneficial effects of Nigella sativa (N. sativa) on RA have been established, it seems that its mechanisms of action have not still been reviewed. The present review is designed to evaluate the effects of N. sativa on RA systematically. We searched these electronic databases until April 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Due to potent anti-inflammatory action, Nigella sativa oil (NSO) and thymoquinone (TQ) were shown to be effective against arthritis, including RA. As some reviews have already highlighted anti-arthritic potential of NSO and TQ elsewhere [ 262 , 263 ], we better addressed some recent progress. For example, NSO (1.82 mL/kg) reduced proinflammatory mediators (such as IL-6) and improved (56%) adjuvant induced-arthritis in the rat model [ 264 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%
“…Due to potent anti-inflammatory action, Nigella sativa oil (NSO) and thymoquinone (TQ) were shown to be effective against arthritis, including RA. As some reviews have already highlighted anti-arthritic potential of NSO and TQ elsewhere [ 262 , 263 ], we better addressed some recent progress. For example, NSO (1.82 mL/kg) reduced proinflammatory mediators (such as IL-6) and improved (56%) adjuvant induced-arthritis in the rat model [ 264 ].…”
Section: Benefits Of Black Cumin On Human Health and Disease Conditionsmentioning
confidence: 99%
“…According to the meta-analyses, Nigella sativa reduces body weight [ 51 , 52 ]. A systematic review by Khabbazi [ 53 ] suggested that Nigella sativa might be effective in the treatment of rheumatoid arthritis, especially in animal and in vitro studies, as well as in humans (a decrease in the disease activity score 28 (DAS28) was especially noted). It is also supposed to alleviate the course of other autoimmune diseases, such as autoimmune encephalomyelitis [ 54 ], ulcerative colitis [ 55 ], and psoriasis [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…SOD, catalase, glutathione peroxidase, and myeloperoxidase play a key role in combating ROS by converting hydrogen peroxide to H20. NS exerts its antioxidant effect by increasing SOD, GPx, and CAT, and decreasing MPO [32,[34][35][36][37]. Moreover, other mechanisms such as upregulation of anti-inflammatory hormone (like adiponectin) [38], reduction of IL-1β and IL-6, and increase in IL-10 are effective in creating anti-inflammatory and antioxidant effects of NS [39,40].…”
Section: Discussionmentioning
confidence: 99%